Effect of Short-Term Free Fatty Acids Elevation on Mitochondrial Function in Skeletal Muscle of Healthy Individuals - Chavez, Alberto O. (The Endocrine Society, 2010)
Context: Mitochondrial dysfunction has been proposed as an underlying mechanism in the pathogenesis of insulin resistance and type 2 diabetes mellitus. Objective: To determine whether mitochondrial dysfunction plays a role in the free fatty acid (FFA)-induced impairment in insulin action in skeletal muscle of healthy subjects. Design: Eleven lean normal glucose tolerant individuals received 8 h lipid and saline infusion on separate days with a euglycemic insulin clamp during the last 2 h. Vastus lateralis muscle biopsies were performed at baseline and after 6 h lipid or saline infusion. Inner mitochondrial membrane potential (Ψ(m)) and mitochondrial mass were determined ex vivo by confocal microscopy. Results: Compared with saline infusion, lipid infusion reduced whole-body glucose uptake by 22% (P < 0.05). Ψ(m) decreased by 33% (P < 0.005) after lipid infusion and the decrement in Ψ(m) correlated with change in plasma FFA after lipid infusion (r = 0.753; P < 0.005). Mitochondrial content and morphology did not change after lipid infusion. No significant changes in genes expression, citrate synthase activity, and total ATP content were observed after either lipid or saline infusion. Conclusions: Short-term physiological increase in plasma FFA concentration in lean normal glucose tolerant subjects induces insulin resistance and impairs mitochondrial membrane potential but has no significant effects on mitochondrial content, gene expression, ATP content, or citrate synthase activity.